Effect of the degree of hydrogenation on the viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane. (29th January 2022) - Schmidt, Patrick S.; Kerscher, Manuel; Klein, Tobias; Jander, Julius H.; Berger Bioucas, Francisco E.; Rüde, Timo; Li, Shao; Stadelmaier, Monika; Hanyon, Samantha; Fathalla, Ramy R.; Bösmann, Andreas; Preuster, Patrick; et al.
Abstract: For the efficient design of hydrogenation and dehydrogenation processes, a comprehensive database for the viscosity, surface tension, and density of mixtures of the diphenylmethane-based liquid organic hydrogen carrier system and the pure intermediate cyclohexylphenylmethane measured by complementary optical and conventional methods and calculated by molecular dynamics simulations at process-relevant temperatures up to 623 K is presented. The simulations employ self-developed force fields including a new one for cyclohexylphenylmethane and reveal surface enrichment and orientation effects influencing the surface tension. Relatively simple correlation and prediction approaches yield accurate representations as function of temperature and degree of hydrogenation ( DoH ) of the mixtures with average absolute relative deviations (AARD) of 0.07% for the density and 2.9% for the surface tension. Application of the extended hard-sphere theory considering the presented accurate density data allows capturing the highly nonlinear DoH -dependent behavior of the dynamic viscosity with an AARD of 2.9%. Graphical abstract: Image 1 Highlights: Experimental data from light scattering and conventional methods up to 573 K. Molecular dynamics simulations show surface orientation and enrichment effects. Wide-range density correlation with average absolute relative deviation of 0.07%. Surface tension represented by empirical model within 2.9%. Strong dependence of dynamic viscosity on mixture composition.